Ethnic, racial and regional inequalities in access to COVID-19 vaccine, testing and hospitalization: Implications for eradication of the pandemic - Ahlberg, Beth Maina; Bradby, Hannah (Frontiers in Sociology, 2022)
The COVID-19 pandemic has made visible inequalities as exemplified by unequal access to COVID-19 vaccine across and within countries; inequalities that are also apparent in rates of testing, disease, hospitalization and death from COVID-19 along class, ethnic and racial lines. For a global pandemic such as the COVID-19 to be effectively addressed, there is a need to reflect on the entrenched and structural inequalities within and between countries. While many countries in the global north have acquired more vaccines than they may need, in the global south many have very limited access. While countries in the global north had largely vaccinated their populations by 2022, those in the global south may not even complete vaccinating 70% of their population to enable them reach the so-called herd immunity by 2024. Even in the global north where vaccines are available, ethnic, racialized and poor working classes are disproportionately affected in terms of disproportionately low rates of infection and death. This paper explores the socio-economic and political structural factors that have created and maintain these disparities. In particular we sketch the role of neoliberal developments in deregulating and financializing the system, vaccine hoarding, patent protection and how this contributes to maintaining and widening disparities in access to COVID-19 vaccine and medication.